Dupla vagy semmi, avagy kockáztassuk-e a talált pénzt? Kísérlet a kockázattal szembeni attitűd mérésére kérdőíves adatfelvételi módszerrel - Szántó, Zoltán; Tóth, István György (Szociológiai Szemle, 2024)
In our paper we have made an attempt to empirically analyse attitudes towards risk. As a starting point of our logic, we have accepted the basic concepts and analytical models of the theory of rational decision-making. After having differentiated between certainty, uncertainty and risk, we have defined three basic types of attitude towards risk, such as: avoidance of risk, neutrality to risk and the liking of risk. What we wanted to find out were the interrelationships to be explored in respect of the empirical types of attitude towards risk, and their socio-demographic determination, on the basis of the relatively little empirical data at our disposal. First of all the theory of rational decision-making was used, to clarify concepts and to build a hypothesis: part of the hypotheses, awaiting empirical control - attitude towards typical risk, and the hypotheses concerning the relationships between attitude towards risk and the extent of the stake, and the size of income - were derived from the theoretical models. The other hypotheses - concerning the sociodemographic interrelationships of attitude towards risk - were worded partly on the basis of empirical results, and partly intuitively. We started our empirical analysis by checking the various parts of hypotheses by relatively simple methods (such as cross tabulation). Of the socio-demographic factors our data seemed to corroborate the effect of school education only partially, the effects of occupation in a differentiated way, whereas age and gender straight away and quite unambiguously on the attitude towards risk. Yet all these results could be accepted with reservations because of the possible effects of composition. Therefore we considered it necessary to do a multi-variable statistical analysis of the data during the course of further analysis, with the help of logistic regression models.